Relationship between Substance Abuse and Suicidal Ideation among Undergraduates in Kwara State, Nigeria: Implications for School Counselling (Journal of Guidance and Counselling Studies, 2025)
This study examined the relationship between substance abuse and suicidal ideation among undergraduates in Kwara State, Nigeria. The descriptive survey of correlational type was adopted for the study. Simple random sampling technique was used to select respondents from three tertiary institutions in Kwara State, Nigeria. The research instrument, titled: “Substance Abuse and Suicidal Ideation Questionnaire (SASIQ)” was used to collect data from the respondents. The findings revealed that there was a significant relationship between substance abuse and suicidal ideation among undergraduates in Kwara State. The findings revealed that substance abuse had no significant relationship with respondent’s age, gender, class level, place of residence, and course of study. Findings also showed that suicidal ideation had no significant relationship with respondent’s gender, class level, place of residence, age and course of study. It was therefore, recommended that undergraduates struggling with substance abuse should seek counselling and support services from professionals in school as this will help to prevent the incidents that could lead to suicidal ideation in tertiary institutions in Kwara State. Education stakeholders, including school administrators, level advisors, counsellors, parents, and health practitioners, should collaborate to develop comprehensive programmes that focus on prevention, early intervention, and support for undergraduates struggling with substance abuse and suicidal ideation, regardless of age, gender, class level, place of residence and course of study.